Social Practices of Literacy and Numeracy Through Culturally Responsif Teaching (CRT) Approach in Sociology Learning - Atik Catur Budiati; Siany Indria Liestyasari; Dwi Astutik; Bagas Narendra Parahita; Riadi Syafutra Siregar; Ghufronudin Ghufronudin (Journal Evaluation in Education (JEE), 2025)
Purpose of Study: This study aims to identify social practices of literacy and numeracy using the CRT approach in Sociology learning. Methodology: This research uses a descriptive qualitative approach with a phenomenology type. The data source consists of focus group discussion (FGD) results, observation, and document analysis. FGD involves sociology teachers in Soloraya, with the purposive sampling technique used to select informants. Observation was carried out directly by observing the sociology learning process in the class. Document analysis includes teaching modules, sociology learning gain, student worksheets, and other learning sets. Data validity was tested using source and method triangulation. Data analysis was done using Interpretative Phenomenology Analysis, encompassing four stages: bracketing, intuiting, analyzing, and describing. Main Findings: The result of the research shows that teachers get a support system from government regulation, the Merdeka Mengajar platform, the learning community, the supervisor, and the subject teacher working group. Each of the parties plays a role that supports CRT-based literacy and numeracy learning. The learning activity can be identified in three things. Firstly, teachers hold the authority to accustom the students to using numeric data in the context of local culture. Secondly, teachers integrate numeric data from local cultures to make learning more relevant and contextual. Thirdly, teachers create an inclusive learning environment by accommodating numeric data in the context of local culture. Novelty/Originality of Study: By applying CRT, sociology teachers teach literacy and numeracy skills and help students see the relevance of these skills in understanding and participating in social change.